Implementação da linguagem R no ensino de Estatística utilizando dados de Saúde Pública - MATOS, Marcos Aurelio de Souza Alves (2023)
We present a practical way to approach the concepts in Descriptive Statistics in High School, using programming language R. The purpose is to take easy the teaching-learning process. The motivation will be through data taken from the Ministry of Health's database, Vigitel, which deals with the surveillance of non-transmissible chronic diseases through telephone survey. We will use the 2015 database, creating problem situations in which the use of R is necessary for the determination of measures of central tendency, dispersion, graphs and data analysis.